Programmes of Industrial Development 1956-61 (Textile and Timber Industries) - Planning Commission (Planning Commission, 1956)
When the First Five Year Plan was published towards the end of 1952, there was brought out at the same time a volume entitled “Programmes of Industrial Development, 1951-56” containing studies of 42 organised industries. In the present volume, there are gathered together statistical data relating to 51 organised industries together with programmes for their expansion during the period of the Second Five Year Plan. Textile machinery and machine tools treated separately in the earlier volume are dealt with under Industrial machinery, and Grinding wheels and Coated abrasives are treated together so that the number of organised industries in this volume comes to 51. These 51 industries account for about 90 per cent of the fixed investment in organised manufacturing industries at the present time.
Government of India Planning Commission